Rice Trade Issues between Japan and Thailand - Chantadansuwan, Sittikorn (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: Thailand, the largest rice exporting country in the world , had expected new rice market opportunities when the Japanese market was liberalized by the Uruguay Round. However, Thailand was unsatisfied with the Japanese rice market access, claiming that the Japanese rice import regime lacked transparency. In particular, Thailand argued that Japan used de facto country specific quotas to determine the in-tariff quota in its minimum access regime. The alleged "country specific quota" prevented Thailand from attaining a market share in the Japanese import rice market, as it should have been able to do. Is the allegation above warranted? Was the Japanese rice import regime in 2001 -- the so-called minimum access regime -- legal under the World Trade Organization (WTO) law? This thesis purports to examine this claim under the WTO legal order of which Japan and Thailand are Members.